The art of frugal hedonism ebook A guide to spending less while enjoying everything more. - Raser-Rowland, Annie (Melliodora Publishing, 2016)
A tweak here, a twiddle there; every strategy in The Art Of Frugal Hedonism has been designed to help you target the most important habits of mind and action needed for living frugally but hedonistically. Apply a couple, and you'll definitely have a few extra dollars in your pocket and enjoy more sunsets. Apply the lot, and you'll wake up one day and realise that you're happier, wealthier, fitter, and more in lust with life than you'd ever thought possible. Never has such a compelling case been made for putting your wallet away and looking around at every other form of pleasure with freshly attentive eyes. Annie and Adam are lifelong cheapskates who operate on the principle that enjoying life is a lot more likely to happen if you learn how to do it on little or no money. Decades of this approach saw them realise they also had more free time, savings, and flexibility than many of their more fiscally-oriented peers. Not to mention smaller ecological footprints, and blissful immunity to a raft of common modern ills, from social isolation to obesity. The Art of Frugal Hedonism reveals their core strategies for lowering your consumption while raising your quality of life. Whether you are already challenging cultural consumption assumptions (but would love a little backup), or are looking for a real kickstart to help you revise your current relationship with spending, there is something in here for you. "The freest and most contented people pretty much follow the advice in The Art of Frugal Hedonism." ~ Clive Hamilton, author of Growth Fetish and co-author of Affluenza. "The Art of Frugal Hedonism is an absolute joy. It is good-natured not pious, humane not self-righteous and a guide to ethical living that makes the impossible possible. I am happy to make this my bible." ~ Christos Tsiolkas, author of The Slap "An invaluable harvest of tips oozing with hedonistic wit and wonder. Packed with ideas about why and how we are to live with less to ensure we have a hell of a lot more." ~ Meg Ulman, co-author of The Art of Free Travel "In an age that is obsessed with consumer trinkets and oblivious to waste, the philosophy of frugal hedonism provides a welcome and necessary antidote. The simplicity of this message is profound. Be frugal and be free." ~ Samuel Alexander, co-director of the Simplicity Institute